Development of Integrated Learning Model Based on Local Culture in Improving the Competence of Kindergarten Children in Medan City - Marbun, Sariana; Nasriah, Nasriah; Ray, Damaiwaty; Simatupang, Dorlince; Simanjuntak, Jasper (Budapest International Research and Critics University, 2021)
This study aims to develop an Integrated Learning Model Based on Local Culture in improving the competence of Kindergarten Children in Medan City. Through Research and Development, researchers developed the Dick & Carey Learning Model Design. This research was conducted in three major stages, namely: 1) Preliminary Study; 2) Development; and 3) Validation Phase. The results of the preliminary research show that: (1) the forms and values of local culture can be integrated into learning in kindergarten; (2) Integrated learning based on local culture can be done in the classroom or outside the classroom; (3) In general, kindergarten teachers in Medan City are very weak in their understanding and skills in developing regional cultural values in learning; 5) Lack of facilities and infrastructure that supports the implementation of integrated learning based on local culture in kindergarten. 6) In general, children's mastery of regional cultural values is very weak. The Learning Design Models developed are: 1) Formulation of indicators of child development achievement; 2) Formulation of learning objectives related to local culture; 3) Development of learning materials and local cultural materials; 4) determination of the steps of learning activities; 5) the determination of media and learning resources, especially for the development of local cultural materials in learning; and 6) Development of assessment instruments.